From Christianity to Islam: an analysis of Ibn Rabban’s approach towards Sira Nabawiyya - Ahmad Sanusi Azmi; Zulhilmi Mohamed Nor; Amiruddin Mohd Sobali; Mohd Yusuf Ismail; Amran Abdul Halim (Department of Theology and Philosophy, Faculty of Islamic Studies, Universiti Kebangsaan Malaysia, 2017)
With the expansion of Muslim territory in the ninth century, non-Muslim communities’ reactions to the denials of the prophethood of Muhammad created an impact on the development of Islamic prophetology. Vigorous refutations from non-Muslim community, specifically the Jews, Christians and Brahmins urged Muslims to develop a solid mechanism in defence of the status of their beloved Prophet. One of the works that has been recognized as an apparatus to defend the Prophet Muhammad veracity is al-Din wa al-Dawla composed by Ibn Rabban, a physician of the Caliph’s court. This study analyses the novelty of his approaches in exploring Sira Nabawiyya and defending the prophethood of Muhammad. The study employed a descriptive, comparative and critical approach where it analyses and extracts the author original approach in explaining the legitimacy of Muhammad’s prophethood and enlightening the Prophet’s biography. The study argues that most of Ibn Rabban arguments in this work are actually developed from the foundations of Biblical scripture. His style of interpreting Biblical passages indicates a possible dependence on Ibn al-Layth’s letter. However, the way in which he presents Quranic references seems not to be in accordance with Ibn al-Layth’s perspective. This is where the novelty of his approach is distinguished. As a result, the study also affirms that Ibn Rabban imposes his own standards of selection and interpretation of Quranic verses when he applies it as reference to the Prophet’s life.